Pengaruh Lingkungan dan Kapasitas Manajerial Terhadap Keputusan Pendanaan Bagi Usaha Kecil Kerajinan 1 di Jawa Timur - Nur Laely; Ana Komari (Universitas 17 Agustus 1945 Surabaya, 2017)
This research talks about the environment of craftsmen, Managerial Capacity andFunding Decision for Small Scale Enterprises in East Java. The population of the studywas 3,711 craftsmen in East Java. Using Slovin formula with a tolerance of 5%, the samplesize was 392 respondents. Test model with Generalized Least Square Estimation (GLS), structural equationmodel (SEM) analysis, proportional random sampling method and Amos 22 software aid,in 392 respondents. The test results show the model (fit) seen from the value of GFI, AGFI,TLI, CFI, RMSEA and CMIN / DF, each of 0.927, 0.914, 0.965, 0.968, 0.072 and 1.284 areall within the expected range of values so that the model can be accepted. The results showed that: 1). There is a direct influence of the craftsman's Environmenton the managerial capacity of the craftsmen by 0.720. 2). There is a direct influence of thecraftsman's Environment on the craftsman's financing decision of 0.679. 3). There is adirect influence of the managerial capacity of the craftsmen on the craftsman's financingdecision of 0.324. 4). There is an indirect influence of the craftsman's Environment on thefinancing decision of the craftsman through the managerial capacity of 0.233. Major indirect linkage between environmental variables of craftsmen and financingvariables of small craft businesses through managerial capacity variables. This indicatesthat the managerial capacity of small craft business will increase, with the management ofthe business environment of the good craftsmen in East Java Province. Keywords: Environment, managerial capacity, funding decision, small business craftsmen